Physical therapy for individuals with amyotrophic lateral sclerosis: current insights - Bello-Haas, Vanina Dal (Degener Neurol Neuromuscul Dis, 2018)
Amyotrophic lateral sclerosis (ALS) is a progressive, neurodegenerative, and inevitably fatal disease. There is no cure for ALS and life expectancy is typically 2–5 years after symptom onset. Despite the lack of a cure and the rapidly progressive nature of the disease, ALS is considered a “treatable disease” and rehabilitation is integral to optimal, comprehensive care. In addition to the other health care professions making up the health care team, physical therapy provides a critical role in the overall management in individuals with ALS. Physical therapy that is tailored to the individual’s needs and goals and focused on addressing symptoms and maximizing function and participation enables people with ALS to live their lives to the fullest and with quality. The purpose of this paper is to review some of the recent ALS research findings that have implications for physical therapy practice.